Analisis Niat Donor Darah Sukarela (DDS) untuk Konseling Menerima Hasil Test di Unit Donor Darah (UDD) PMI Kabupaten Semarang - Wulandari, Siti; Widjanarko, Bagoes; Cahyo, Kusyogo (Jurnal Promosi Kesehatan Indonesia, 2015)
ABSTRACTBold Blood Donor are Present On The UDD PMI Semarang Reactive Screening Result For Counseling?Every year the number of blood donations in PMI Semarang district there is an increase. Donated blood at the Red Cross will do blood screening. Blood screening will be undertaken are 4 parameters (HIV, Syphillis, Hepatitis B, Hepatitis C). DDS in donating their blood found that in a healthy state at the time of screening and the result is reactive, the attitudes of different DDS would anyone want to do is present for counseling and some do not want to attend. The purpose of this research is to know the intentions of doing counselling in UDD PMI Semarang. This type of research is Explanatory research with cross sectional approach. The subject of research is the blood donors in PMI Semarang with a total sample of 297 people. The results showed 70,0% most of the DDS is not the intention to undertake counseling screening results. Results of the analysis show that variable attitude bivariat DDS when results of blood screening has significant relationship reactive with the intention of doing a counseling screening. While the results of the multivariate shows availability of facilities and means in UDD PMI will make intentions DDS did better counseling of 3,506 times rather than the availability of facilities and means of UDD PMI which is less available.Keywords: DDS, counseling, blood screening